Association between Sex Hormone and Blood Uric Acid in Male Patients with Type 2 Diabetes - Wen Cao; Ren-Dong Zheng; Shu-Hang Xu; Yao-Fu Fan; Hong-Ping Sun; Chao Liu (International Journal of Endocrinology)
The association between serum uric acid (SUA) level and sexual dysfunction in patients with diabetes is not well characterized. Type 2 diabetes mellitus (T2DM) causes metabolic disorders, including abnormal serum uric acid (SUA) levels. In this study, we enrolled 205 male patients with T2DM and investigated the relationship between sex hormone levels and SUA. Patients were divided into four groups based on SUA quartiles. On the other hand, based on the total testosterone (TT) level, patients were divided into three groups; SUA and other laboratory indices were determined. Increase in SUA level was significantly associated with decreased levels of TT, luteinizing hormone, follicle-stimulating hormone, sex hormone-binding globulin, and increased levels of dehydroepiandrosterone, age, body mass index (BMI), waist circumference, glycated hemoglobin, serum creatinine, and HOMA-IR levels. SUA, waist circumference, BMI, and HOMA-IR showed a negative correlation with TT level, while age showed a positive correlation with TT level. SUA and body mass index were found to be risk factors for gonadal dysfunction. Therefore, we conclude that hypogonadism of male patients with T2DM is related to SUA level.